Hunting young white dwarfs at the Center of Planetary Nebulae - Ahumada, Javier Alejandro (2019)
We present Gemini-South observations of nine faint and extended planetary nebulae (PNe). Using direct images taken with the spectrograph Gemini-South multi-object spectrograph (GMOS), we built the (u¢-g¢) versus (g¢-r¢) diagrams of the stars in the observed areas which allowed us to consider their geometrical positions and identify the probable central stars of the nebulae. Our stellar spectra of seven stars, also taken with GMOS, indicate that four (and probably two more) objects are white dwarfs of the DAO subtype. Moreover, the white dwarf status of the four stars is confirmed by the parameters Teff and log g derived with the help of theoretical stellar spectra. Given this evidence, we propose that these hot stars are the central ionizing sources of the nebulae. With this work we hope to help improve the current scarce statistics on central white dwarfs in PNe.